Pendidikan Vis a Vis Sosial Budaya: Dialektika antara Pendidikan Islam dengan Perubahan Sosial Budaya - Sultoni, Agus (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Knowledge is part of culture, while culture is the result of human activity in order to maintain life through the knowledge it acquires. Institutionalized education is a systematic and organized forum for knowledge, where the style of education reflects the socio-cultural conditions in which it develops. So there is a double movement between education and socio-culture that influence each other and there should be no domination of each other. From here, it appears that there is a dialectical relationship between education and sociocultural changes that have colored the history of human civilization from time totime. This paper is intended to describe the role of Islamic education in the context of Indonesia, which in its journey greatly influences the formation of socio-culture to this day. The big concern is that although globalization has become a necessity, the style of education in Indonesia should not be uprooted from the socio-cultural roots where it originates